2018
DOI: 10.1093/rpd/ncy143
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia, Prostate and Skin Cancer in Acute Radiation Syndrome Survivor After the 1986 Chernobyl Nuclear Accident: Case Report

Abstract: The development of hemoblastosis is often associated with the influence of various genotoxic unfavorable factors, in particular, with the effect of ionizing radiation. This article presents a case report of acute myeloid leukemia (AML) in a patient who was involved in the 1986 accident at the Chernobyl Nuclear Power Plant and suffered an acute radiation syndrome of degree II severity. Based on clinical and cytogenetic dosimetry, the average absorbed radiation dose to the whole body was estimated to be 4.3 Gy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Alterations at the band 1q21 and CKS1B hyperexpression were associated with poor prognosis in plasma-cell dyscrasias [ 33 ]. Unlike this clone, malignant clones are typically characterized by a high frequency and imbalanced karyotype, such as the acute malignant myeloma clone recently reported by us in another Chernobyl victim [ 34 ], however, the patient of the present study does not manifest any signs of hematooncological diseases. Since clone t(1;15) was only detected in the 2019 year, the dynamics of its frequency remained unknown.…”
Section: Discussionmentioning
confidence: 56%
“…Alterations at the band 1q21 and CKS1B hyperexpression were associated with poor prognosis in plasma-cell dyscrasias [ 33 ]. Unlike this clone, malignant clones are typically characterized by a high frequency and imbalanced karyotype, such as the acute malignant myeloma clone recently reported by us in another Chernobyl victim [ 34 ], however, the patient of the present study does not manifest any signs of hematooncological diseases. Since clone t(1;15) was only detected in the 2019 year, the dynamics of its frequency remained unknown.…”
Section: Discussionmentioning
confidence: 56%
“…Repeated chromosomal analyses of the sternal and iliac BM showed that various non-clonal complex abnormalities from 20% to 80% in a single cell (25). In a victim of the 1986 accident at Chernobyl, a very high frequency of translocations was observed over 30 years (26). In a recent report from the JSHCT, TBI was administered to 40 of 42 recipients who experienced autologous recovery with chromosomal abnormalities (24).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to radioactive materials has caused carcinoma among thousands of people. Although most of the patients have suffered from Thyroid Cancer [4][5][6], other cases such as Acute Myeloid Leukemia, Prostate and Skin Cancer have also been reported [7]. The memory of Fukushima Daiichi nuclear accident in 2011 is still fresh among the mindset of people across the globe.…”
Section: Introductionmentioning
confidence: 99%